Another Story of the Masculine Genesis of Political Life? Locke on Family, Marriage and the Conjugal Society - Chou, Chiayu (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2025)
Locke's seemingly paradoxical patriarchal stance has led certain commentators to label him as a “patriarchal anti-patriarchalist,” or even one of the “equality radicals” of the late seventeenth century. Rather than falling into this binary between a “patriarchalist reading of Locke” and an “egalitarian reading of Locke,” this essay aims to reveal the complexities of Locke’s political thought. While the two interpretations come to opposite conclusions, both focus on two aspects of Locke's work: the residual patriarchalism evident in his accounts of marriage, and the separation of family from civil society. Despite Locke’s accounts of male dominance within the family based on Scripture, this essay argues that, considering the practices of his day, Locke provides relatively progressive accounts of women's rights and the marriage contract, specifically women’s entitlement to divorce and property ownership. This essay first revisits Locke’s alleged “residual patriarchalism” by exploring his interpretation of Genesis to reassess Eve’s role in relation to Adam. I argue that Locke's biblical analysis reveals an often-overlooked egalitarian undertone. The second section investigates Locke’s accounts of women’s rights and conjugal society, contending that women are not confined to a private sphere, but are granted significant rights that challenge traditional patriarchal norms. In conclusion, while not supporting either the “patriarchalist reading” or the “egalitarian reading,” this essay suggests that Locke’s contributions can be interpreted as challenging patriarchal structures.